How vividness and review quality influence purchase intention in mobile shopping - Anh Thi Van Pham; Trung Minh Ngo (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This study investigates the effects of vividness (a web/app stimulus) and review quality (a situational stimulus) on consumers’ risk perception and purchase intention in Vietnamese mobile shopping. In doing so, we analyzed quantitative research involving 400 respondents using Structural Equation Modeling (SEM). The findings show that a compelling and sociable experience has a significant effect on mitigating consumers’ perceived risk while increasing their purchase intention. Creating the experience involves utilizing vivid features and high-quality online reviews from previous consumers. These results enrich the existing literature by supporting the use of the SOR model and introducing presence as a stimulus to explain consumers’ risk perceptions and purchase behaviors. Furthermore, the study provides valuable guidance in app design that can stimulate purchases while lowering online perceived risk.